Three graphs that show where the coronavirus death rate is heading - Dorling, D (The Conversation Trust (UK) Limited, 2020)
On April 7, The Conversation published three graphs showing the rise of deaths from COVID-19 in seven countries. What we could not have known then was that April 7 was the point at which the peak, or at least the first peak, in mortality in England and Wales was reached.